Perovskite solar cell with barrier layer and preparation method thereof
Patent Information
- Application Number
- CN202510306626.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2026-09-22
AI Technical Summary
[0002]钙钛矿太阳能电池受限于其稳定性问题,一直难以商业化
[0005]本发明以壳聚糖为原料,合成了一种壳聚糖-聚碘超分子材料,并将其用于钙钛矿太阳能电池中作为碘离子迁移的阻挡层,它能够有效抑制钙钛矿太阳能电池工作状态下的碘离子迁移,并且在其不工作的时候释放碘离子进行有效自修复钙钛矿中的碘空位。壳聚糖其本身自带的氨基能够通过氢键作用加强与钙钛矿吸光层的作用,并且有效钝化钙钛矿吸光层表面缺陷。而且,壳聚糖其本身的疏水性能够有效隔绝水氧,提高钙钛矿太阳能电池的耐水氧能力。
Smart Images

Figure CN122803506A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite solar cell technology, and specifically relates to a perovskite solar cell with a barrier layer and its preparation method. Background Technology
[0002] Perovskite solar cells have been hampered by their stability issues, hindering their commercialization. The reasons for the instability of perovskite solar cells are varied, including decomposition due to water vapor and oxygen in the air, decay caused by temperature, and iodine ion migration under their own electric field during operation. Summary of the Invention
[0003] The technical problem to be solved by the present invention is to provide a perovskite solar cell with a barrier layer and a method for preparing the same, which improves the problem of iodine ion migration in perovskite solar cells, enhances their resistance to water and oxygen, and improves their photoelectric conversion efficiency.
[0004] The present invention is implemented as follows: a perovskite solar cell with a barrier layer is provided, the internal structure of which includes a transparent conductive electrode, a hole transport layer, a perovskite light-absorbing layer, a barrier layer, an electron transport layer and a metal electrode stacked from top to bottom, wherein the barrier layer contains a chitosan-polyiodine supramolecular compound synthesized by the reaction of chitosan and iodine.
[0005] This invention synthesizes a chitosan-polyiodine supramolecular material using chitosan as a raw material and applies it to perovskite solar cells as a barrier layer against iodine ion migration. It effectively inhibits iodine ion migration during the operation of the perovskite solar cell and releases iodine ions to effectively repair iodine vacancies in the perovskite when the cell is not in operation. The amino groups inherent in chitosan can strengthen the interaction with the perovskite light-absorbing layer through hydrogen bonding and effectively passivate surface defects in the perovskite light-absorbing layer. Furthermore, the hydrophobicity of chitosan effectively isolates water and oxygen, improving the water and oxygen resistance of the perovskite solar cell.
[0006] Furthermore, a buffer layer is provided between the hole transport layer and the perovskite light-absorbing layer, and the buffer layer is made of NiOx-NiI2 material.
[0007] This invention adds a NiOx-NiI2 layer as a buffer layer between the hole transport layer and the perovskite light-absorbing layer. On the one hand, this reduces the energy level barrier between the hole transport layer and the perovskite light-absorbing layer. On the other hand, it can act as an iodine source to promptly repair iodine vacancies in the perovskite light-absorbing layer caused by ion migration when the perovskite solar cell is working.
[0008] Furthermore, the transparent conductive electrode is made of any one of ITO, FTO, and AZO, and the metal electrode is made of any one of Au, Ag, Cu, and Al.
[0009] Furthermore, the hole transport layer is prepared using NiO as the material. x CuGaO3, CuAlO2, VO2, Cu x Any one of O.
[0010] Furthermore, the material used to prepare the perovskite light-absorbing layer contains any one of the anions of I, Br, and Cl elements, as well as organic cations containing MA or FA.
[0011] Furthermore, the electron transport layer is prepared from any one of the inorganic materials selected from SnO, ZnO, TiO2, ZnS, CdS, In2S3, MoS2, and SnS2, or from any one of the organic materials selected from PDI, NDI, PDIN, and PDINO.
[0012] This invention is implemented as follows, and also provides a method for fabricating a perovskite solar cell with a barrier layer as described above, comprising the following steps: Step 1: The substrate containing the transparent conductive electrode is ultrasonically cleaned sequentially with deionized water, isopropanol, and acetone, then dried with nitrogen and treated with UV-Ozone for 30 minutes. Step 2: Prepare a hole transport layer on the cleaned transparent conductive electrode surface; Step 3: Prepare a buffer layer composed of NiOx-NiI2 material on the hole transport layer; Step 4: Prepare a perovskite light-absorbing layer on the buffer layer; Step 5: Prepare a barrier layer composed of chitosan-polyiodine supramolecular structure on the perovskite light-absorbing layer; Step 6: Sequentially fabricate an electron transport layer and a metal electrode on the barrier layer to obtain a perovskite solar cell.
[0013] Compared with the prior art, the perovskite solar cell with a barrier layer and its preparation method of the present invention have the following characteristics: 1. In the perovskite solar cell of this invention, chitosan-polyiodine supramolecular material is used as a barrier layer. This effectively inhibits iodine ion migration during the operation of the perovskite solar cell, thereby reducing defects and improving its efficiency. When the perovskite solar cell is not in operation, the chitosan-polyiodine supramolecular material can release iodine ions to effectively repair iodine vacancies without its own electric field, thus improving the stability of the perovskite solar cell. The amino groups inherent in the chitosan-polyiodine supramolecular material can strengthen the interaction with the perovskite light-absorbing layer through hydrogen bonding and effectively passivate surface defects in the perovskite light-absorbing layer. The chitosan-polyiodine supramolecular material has good hydrophobicity, effectively isolating water and oxygen, and improving the water and oxygen resistance of the perovskite solar cell.
[0014] 2. This invention adds a NiOx-NiI2 layer as a buffer layer between the hole transport layer and the organic perovskite layer. The addition of NiI2 improves the energy level barrier between the hole transport layer and the perovskite light-absorbing layer, enhances the conductivity of the hole transport layer, and improves the overall transport efficiency. Simultaneously, it can also promptly repair defects caused by iodine ion migration during the operation of the perovskite solar cell, improving its operational stability. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the internal structure of a perovskite solar cell with a barrier layer according to Embodiment 1 of the present invention; Figure 2 This is a schematic diagram of the internal structure of a perovskite solar cell with a barrier layer according to Embodiment 2 of the present invention; Figure 3 This is a comparison chart of the performance of perovskite solar cells IV prepared in Example 4 and Comparative Example 1 of the present invention; Figure 4 This is a comparison chart showing the aging test results of the perovskite solar cells prepared in Example 4 and Comparative Example 1 of the present invention. Detailed Implementation
[0016] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0017] Example 1
[0018] Please refer to Figure 1 As shown, a preferred embodiment of the perovskite solar cell with a barrier layer of the present invention has an internal structure comprising, from top to bottom, a transparent conductive electrode 1, a hole transport layer 2, a perovskite light-absorbing layer 3, a barrier layer 4, an electron transport layer 5, and a metal electrode 6. The barrier layer 4 contains a chitosan-polyiodine supramolecular compound synthesized by the reaction of chitosan and iodine.
[0019] The transparent conductive electrode 1 is made of any one of ITO, FTO, and AZO, and the metal electrode 6 is made of any one of Au, Ag, Cu, and Al.
[0020] The hole transport layer 2 is made of NiO. x CuGaO3, CuAlO2, VO2, Cu x Any one of O.
[0021] The perovskite light-absorbing layer 3 is prepared by a material containing any one of the anions of I, Br, or Cl, as well as an organic cation containing MA or FA.
[0022] The electron transport layer 5 is prepared from any one of the inorganic materials selected from SnO, ZnO, TiO2, ZnS, CdS, In2S3, MoS2, and SnS2, or from any one of the organic materials selected from PDI, NDI, PDIN, and PDINO.
[0023] The electron transport layer 5 has a film thickness of 10nm to 100nm, and the metal electrode has a film thickness of 50nm to 200nm.
[0024] Example 2
[0025] Please refer to Figure 2 As shown, the second embodiment of the perovskite solar cell with a barrier layer of the present invention differs from the first embodiment in that a buffer layer 7 is further provided between the hole transport layer 2 and the perovskite light-absorbing layer 3, and the buffer layer 7 is made of NiOx-NiI2 material.
[0026] The other structures are the same as those in Example 1, and will not be described again.
[0027] Example 3
[0028] This invention also discloses a method for fabricating a perovskite solar cell with a barrier layer as described above, comprising the following steps: Step 1: The substrate containing the transparent conductive electrode 1 is ultrasonically cleaned sequentially with deionized water, isopropanol, and acetone, then dried with nitrogen and treated with UV-Ozone for 30 minutes.
[0029] Step 2: Prepare hole transport layer 2 on the cleaned transparent conductive electrode 1.
[0030] Step 3: Prepare a buffer layer 7 composed of NiOx-NiI2 material on hole transport layer 2.
[0031] Step 4: Prepare perovskite light-absorbing layer 3 on buffer layer 7.
[0032] Step 5: Prepare a barrier layer 4 composed of chitosan-polyiodine supramolecular on the perovskite light-absorbing layer 3.
[0033] Step 6: Sequentially fabricate electron transport layer 5 and metal electrode 6 on barrier layer 4 to obtain perovskite solar cell.
[0034] The following specific embodiments further illustrate the fabrication method of the perovskite solar cell with a barrier layer of the present invention.
[0035] Example 4
[0036] The first embodiment of the method for fabricating a perovskite solar cell with a barrier layer according to the present invention includes the following steps: Step 11: The substrate of the 2.5*2.5cm indium tin oxide (ITO) transparent conductive electrode 1 is ultrasonically cleaned with deionized water, isopropanol and acetone in sequence for 15 minutes each, then dried with nitrogen and UV treated for 30 minutes.
[0037] Step 12: Dissolve 9g of nickel(II) nitrate hexahydrate in 120mL of water and stir at room temperature to obtain a clear green solution. Then add 1M sodium hydroxide solution until the pH value is 10. After stirring for 10 minutes, centrifuge to collect the green precipitate. Wash it three times with deionized water and ethanol respectively. Dry the green powder at 80℃ for 12h and then calcine it at 275℃ for 2h to obtain a dark gray powder. Take 200mg of this powder and 30mg of NiI2 powder and dissolve them together in 10mL of DMF to obtain a 3mg / mL NiOx-NiI2 solution.
[0038] Step 13: Dissolve 200 mg of nickel nitrate in 10 mL of ethanol to obtain a nickel nitrate solution of 20 mg / mL. Filter the solution using a PVDF filter. Spin-coat 1 mL of the 20 mg / mL nickel nitrate solution onto the cleaned ITO layer. Then anneal at 250 °C for 60 min to obtain hole transport layer 2 (HTL layer).
[0039] Step 14: Take 1 mL of the prepared NiOx-PbI2 solution and drop it onto the surface of hole transport layer 2. Spin coat at 5000 rpm for 30 s, then anneal at 100 °C for 10 min to obtain NiOx-PbI2 buffer layer 7.
[0040] Step 15: Dissolve 18 mg of CsI, 26.7 mg of MABr, 199.8 mg of FAI, 580.9 mg of PbI2, and 87.4 mg of PbBr2 in 1 mL of a mixed solvent of DMF:DMSO = 4:1 to obtain a perovskite precursor solution. Spin coat the perovskite precursor solution onto the buffer layer 7. During the spin coating process, add the antisolvent CB dropwise. After coating, anneal at 120 °C for 30 min to obtain the perovskite light-absorbing layer 3.
[0041] Step 16: Take 1.00 g of chitosan, add 100 mL of ultrapure water to fully swell, add 1.2 mL of glacial acetic acid to obtain a transparent viscous solution; slowly add 20 mL of 1.8 mol / L potassium iodide solution, slowly add 1.2 mol / L iodine solution, stir at 25~100℃ for 1 h; slowly pour the reaction mixture into anhydrous ethanol, stir for 1 h to allow the product to precipitate completely, filter out the product, wash and dry to obtain chitosan-polyiodine supramolecular compound; take 0.5 mg of chitosan-polyiodine supramolecular compound and dissolve it in 1 mL of isopropanol to obtain the desired chitosan-polyiodine supramolecular solution; spin-coat it onto the surface of perovskite light-absorbing layer 3 at 3000 rpm for 30 s, anneal at 100℃ for 5 min to obtain chitosan-polyiodine supramolecular barrier layer 4.
[0042] Step 17: Add 30 μL of PC with a concentration of 20 mg / mL 61 BM's CB solution was dropped onto chitosan-polyiodine supramolecular barrier layer 4 and spin-coated at 2000 rpm for 30 s. 70 μL of 0.5 mg / mL BCP IPA solution was then dropped onto PC. 61 On the BM layer, spin coating is performed at 5000 rpm for 30 s to obtain electron transport layer 5 (ETL layer).
[0043] Step 18: Deposit an electrode Au on the surface of electron transport layer 5, and a metal electrode 6 with a thickness of 60 nm.
[0044] Example 5
[0045] A second embodiment of the method for fabricating a perovskite solar cell with a barrier layer according to the present invention includes the following steps: Step 21: The substrate of the 2.5*2.5cm indium tin oxide (ITO) transparent conductive electrode 1 is ultrasonically cleaned with deionized water, isopropanol and acetone in sequence for 15 minutes each, then dried with nitrogen and UV treated for 30 minutes.
[0046] Step 22: Dissolve 9g of nickel(II) nitrate hexahydrate in 120mL of water and stir at room temperature to obtain a clear green solution. Then add 1M sodium hydroxide solution until the pH value is 10. After stirring for 10 minutes, centrifuge to collect the green precipitate. Wash it three times with deionized water and ethanol respectively. Dry the green powder at 80℃ for 12h and then calcine it at 275℃ for 2h to obtain a dark gray powder. Take 200mg of this powder and 30mg of NiI2 powder and dissolve them together in 10mL of DMF to obtain a 3mg / mL NiOx-NiI2 solution.
[0047] Step 23: Dissolve 200 mg of nickel nitrate in 10 mL of ethanol to obtain a nickel nitrate solution of 20 mg / mL. Filter the solution using a PVDF filter. Spin-coat 1 mL of the 20 mg / mL nickel nitrate solution onto the cleaned ITO layer. Then anneal at 250 °C for 60 min to obtain hole transport layer 2 (HTL layer).
[0048] Step 24: Take 1 mL of the prepared NiOx-PbI2 solution and drop it onto the surface of the hole transport layer. Spin coat it at 5000 rpm for 30 s, and then anneal it at 100 °C for 10 min to obtain the NiOx-PbI2 buffer layer 7.
[0049] Step 25: Dissolve 599 mg of PbI2, 172 mg of MAI, 39 mg of PbCl2 and 46.4 mg of FAI in a mixed solution of 300 μL of DMSO and 700 μL of GBL, and stir at 53 °C for 12 h to obtain a perovskite precursor solution; add 50 μL of the perovskite precursor solution to the buffer layer 7, spin coat at 1500 rpm for 20 s, and then spin coat at 3500 rpm for 40 s; in the last 15 seconds of spin coating, rapidly drop 900 μL of toluene into the film, and finally anneal at 100 °C for 6 minutes to obtain the perovskite light-absorbing layer 3.
[0050] Step 26: Take 1.00 g of chitosan, add 100 mL of ultrapure water to fully swell, add 1.2 mL of glacial acetic acid to obtain a transparent viscous solution; slowly add 20 mL of 1.8 mol / L potassium iodide solution, slowly add 1.2 mol / L iodine solution, stir at 25~100℃ for 1 h; slowly pour the reaction mixture into anhydrous ethanol, stir for 1 h to allow the product to precipitate completely, filter out the product, wash and dry to obtain chitosan-polyiodine supramolecular compound; take 0.5 mg of chitosan-polyiodine supramolecular compound and dissolve it in 1 mL of isopropanol to obtain the desired chitosan-polyiodine supramolecular solution; spin-coat it onto the surface of perovskite light-absorbing layer 3 at 3000 rpm for 30 s, anneal at 100℃ for 5 min to obtain chitosan-polyiodine supramolecular barrier layer 4.
[0051] Step 27: Add 30 μL of PC with a concentration of 20 mg / mL 61 BM's CB solution was dropped onto chitosan-polyiodine supramolecular barrier layer 4 and spin-coated at 2000 rpm for 30 s. 70 μL of 0.5 mg / mL BCP IPA solution was then dropped onto PC. 61 On the BM layer, spin coating is performed at 5000 rpm for 30 s to obtain electron transport layer 5 (ETL layer).
[0052] Step 28: Deposit an electrode Au on the surface of electron transport layer 5, and a metal electrode 6 with a thickness of 60 nm.
[0053] Example 6
[0054] A third embodiment of the method for fabricating a perovskite solar cell with a barrier layer according to the present invention includes the following steps: Step 31: The substrate of the 2.5*2.5cm indium tin oxide (ITO) transparent conductive electrode 1 is ultrasonically cleaned with deionized water, isopropanol and acetone in sequence for 15 minutes each, then dried with nitrogen and UV treated for 30 minutes.
[0055] Step 32: Dissolve 9g of nickel(II) nitrate hexahydrate in 120mL of water and stir at room temperature to obtain a clear green solution. Then add 1M sodium hydroxide solution until the pH value is 10. After stirring for 10 minutes, centrifuge to collect the green precipitate. Wash it three times with deionized water and ethanol respectively. Dry the green powder at 80℃ for 12h and then calcine it at 275℃ for 2h to obtain a dark gray powder. Take 200mg of this powder and 30mg of NiI2 powder and dissolve them together in 10mL of DMF to obtain a 3mg / mL NiOx-NiI2 solution.
[0056] Step 33: Dissolve 200 mg of nickel nitrate in 10 mL of ethanol to obtain a nickel nitrate solution of 20 mg / mL. Filter the solution using a PVDF filter. Spin-coat 1 mL of the 20 mg / mL nickel nitrate solution onto the cleaned ITO layer. Then anneal at 250 °C for 60 min to obtain hole transport layer 2 (HTL layer).
[0057] Step 34: Take 1 mL of the prepared NiOx-PbI2 solution and drop it onto the surface of hole transport layer 2. Spin coat at 5000 rpm for 30 s, then anneal at 100 °C for 10 min to obtain NiOx-PbI2 buffer layer 7.
[0058] Step 35: Spin-coat a DMF solution of PbI2 onto the surface of the NiOx-NiI2 buffer layer 7, anneal at 90°C for 30 min, then vapor-deposit CsI on it with a thickness of 400 nm, and anneal at 200°C for 5 min to obtain the inorganic CsPbI3 perovskite light-absorbing layer 3.
[0059] Step 36: Take 1.00 g of chitosan, add 100 mL of ultrapure water to fully swell, add 1.2 mL of glacial acetic acid to obtain a transparent viscous solution; slowly add 20 mL of 1.8 mol / L potassium iodide solution, slowly add 1.2 mol / L iodine solution, stir at 25~100℃ for 1 h; slowly pour the reaction mixture into anhydrous ethanol, stir for 1 h to allow the product to precipitate completely, filter out the product, wash and dry to obtain chitosan-polyiodine supramolecular compound; take 0.5 mg of chitosan-polyiodine supramolecular compound and dissolve it in 1 mL of isopropanol to obtain the desired chitosan-polyiodine supramolecular solution; spin-coat it onto the surface of perovskite light-absorbing layer 3 at 3000 rpm for 30 s, anneal at 100℃ for 5 min to obtain chitosan-polyiodine supramolecular barrier layer 4.
[0060] Step 37: Add 30 μL of PC with a concentration of 20 mg / mL. 61 BM's CB solution was dropped onto chitosan-polyiodine supramolecular barrier layer 4 and spin-coated at 2000 rpm for 30 s. 70 μL of 0.5 mg / mL BCP IPA solution was then dropped onto PC. 61 On the BM layer, spin coating is performed at 5000 rpm for 30 s to obtain electron transport layer 5 (ETL layer).
[0061] Step 38: Deposit an electrode Au on the surface of electron transport layer 5, and a metal electrode 6 with a thickness of 60 nm.
[0062] Comparative Example 1 The first comparative example of the method for fabricating a perovskite solar cell with a barrier layer according to the present invention includes the following steps: Step D1: The substrate of the 2.5*2.5cm indium tin oxide (ITO) transparent conductive electrode 1 is ultrasonically cleaned with deionized water, isopropanol and acetone in sequence for 15 minutes each, then dried with nitrogen and UV treated for 30 minutes.
[0063] Step D2: Dissolve 200 mg of nickel nitrate in 10 mL of ethanol to obtain a nickel nitrate solution of 20 mg / mL. Filter the solution using a PVDF filter. Spin-coat 1 mL of the 20 mg / mL nickel nitrate solution onto the cleaned ITO layer. Then anneal at 250 °C for 60 min to obtain hole transport layer 2 (HTL layer).
[0064] Step D3: Dissolve 18 mg of CsI, 26.7 mg of MABr, 199.8 mg of FAI, 580.9 mg of PbI2, and 87.4 mg of PbBr2 in 1 mL of a mixed solvent of DMF:DMSO = 4:1 to obtain a perovskite precursor solution. Coat the perovskite precursor solution onto the hole transport layer 2 by spin coating. Add the antisolvent CB dropwise during the spin coating process. After coating, anneal at 120 °C for 30 min to obtain the perovskite light-absorbing layer 3.
[0065] Step D4: Add 30 μL of PC with a concentration of 20 mg / mL 61 BM's CB solution was dropped onto the perovskite light-absorbing layer 3 and spin-coated at 2000 rpm for 30 s. Then, 70 μL of a 0.5 mg / mL BCP IPA solution was dropped onto the PC. 61 On the BM layer, spin coating is performed at 5000 rpm for 30 s to obtain electron transport layer 5 (ETL layer).
[0066] Step D5: Deposit an electrode Au on the surface of electron transport layer 5, and a metal electrode 6 with a thickness of 60 nm.
[0067] The perovskite solar cells prepared in Example 4 and Comparative Example 1 were subjected to IV performance testing and aging testing, respectively, and the results were as follows: Figure 3 The IV performance test comparison curves shown are as follows: Figure 4 The aging test effect comparison curves are shown.
[0068] from Figure 3 It can be observed that the addition of the chitosan-polyiodine barrier layer and the NiOx-NiI2 buffer layer can effectively improve the short-circuit current density of the perovskite solar cell, thereby increasing the conversion efficiency of the perovskite solar cell from 16.46% to 17.61%. This indicates that the chitosan-polyiodine supramolecular structure can effectively passivate the surface defects of the perovskite light-absorbing layer, promote the extraction and transport of charge carriers, and reduce carrier recombination at the interface.
[0069] from Figure 4 It can be observed that after aging for 2000 hours in an environment of 60℃ and 60%RH, the perovskite solar cell prepared in Example 4 only showed a 7% degradation, while the perovskite solar cell prepared in Comparative Example 1 showed a 71.4% degradation. This demonstrates that the addition of the chitosan-polyiodine barrier layer and the NiOx-NiI2 buffer layer can effectively block water and oxygen, prevent iodine ion migration, and repair defects caused by iodine ion migration, thereby improving the stability of the perovskite solar cell.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A perovskite solar cell with a barrier layer, characterized in that, Its internal structure includes a transparent conductive electrode, a hole transport layer, a perovskite light-absorbing layer, a blocking layer, an electron transport layer, and a metal electrode stacked from top to bottom. The blocking layer contains a chitosan-polyiodine supramolecular compound synthesized by the reaction of chitosan and iodine.
2. The perovskite solar cell with a barrier layer as described in claim 1, characterized in that, A buffer layer is also provided between the hole transport layer and the perovskite light-absorbing layer. The buffer layer is made of NiOx-NiI2 material.
3. The perovskite solar cell with a barrier layer as described in claim 2, characterized in that, The transparent conductive electrode is made of any one of ITO, FTO, and AZO, and the metal electrode is made of any one of Au, Ag, Cu, and Al.
4. The perovskite solar cell with a barrier layer as described in claim 2, characterized in that, The hole transport layer is prepared using NiO. x CuGaO3, CuAlO2, VO2, Cu x Any one of O.
5. The perovskite solar cell with a barrier layer as described in claim 2, characterized in that, The perovskite light-absorbing layer is prepared by a material containing any one of the anions of I, Br, or Cl, as well as an organic cation containing MA or FA.
6. The perovskite solar cell with a barrier layer as described in claim 2, characterized in that, The electron transport layer is prepared from any one of the inorganic materials selected from SnO, ZnO, TiO2, ZnS, CdS, In2S3, MoS2, and SnS2, or from any one of the organic materials selected from PDI, NDI, PDIN, and PDINO.
7. A method for fabricating a perovskite solar cell with a barrier layer as described in any one of claims 2 to 6, characterized in that, The steps include the following: Step 1: The substrate containing the transparent conductive electrode is ultrasonically cleaned sequentially with deionized water, isopropanol, and acetone, then dried with nitrogen and treated with UV-Ozone for 30 minutes. Step 2: Prepare a hole transport layer on the cleaned transparent conductive electrode surface; Step 3: Prepare a buffer layer composed of NiOx-NiI2 material on the hole transport layer; Step 4: Prepare a perovskite light-absorbing layer on the buffer layer; Step 5: Prepare a barrier layer composed of chitosan-polyiodine supramolecular on the perovskite light-absorbing layer; Step 6: Sequentially fabricate an electron transport layer and a metal electrode on the barrier layer to obtain a perovskite solar cell.
8. The method for fabricating a perovskite solar cell with a barrier layer as described in claim 7, characterized in that, The steps include the following: Step 11: Clean the substrate of the 2.5*2.5cm indium tin oxide (ITO) transparent conductive electrode by ultrasonic cleaning with deionized water, isopropanol and acetone in sequence for 15 minutes each, then dry it with nitrogen and UV treat it for 30 minutes. Step 12: Dissolve 9g of nickel(II) nitrate hexahydrate in 120mL of water and stir at room temperature to obtain a clear green solution. Then add 1M sodium hydroxide solution until the pH value is 10. After stirring for 10 minutes, centrifuge to collect the green precipitate. Wash it three times with deionized water and ethanol respectively. Dry the green powder at 80℃ for 12h and then calcine it at 275℃ for 2h to obtain a dark gray powder. Take 200mg of this powder and 30mg of NiI2 powder and dissolve them together in 10mL of DMF to obtain a 3mg / mL NiOx-NiI2 solution. Step 13: Dissolve 200 mg of nickel nitrate in 10 mL of ethanol to obtain a nickel nitrate solution of 20 mg / mL. Filter the solution through a PVDF filter. Spin-coat 1 mL of the 20 mg / mL nickel nitrate solution onto the cleaned ITO layer. Then anneal at 250 °C for 60 min to obtain the hole transport layer (HTL layer). Step 14: Take 1 mL of the prepared NiOx-PbI2 solution and drop it onto the surface of the hole transport layer. Spin coat it at 5000 rpm for 30 s, then anneal it at 100 °C for 10 min to obtain the NiOx-PbI2 buffer layer. Step 15: Dissolve 18 mg of CsI, 26.7 mg of MABr, 199.8 mg of FAI, 580.9 mg of PbI2, and 87.4 mg of PbBr2 in 1 mL of a mixed solvent of DMF:DMSO = 4:1 to obtain a perovskite precursor solution. Spin coat the perovskite precursor solution onto the buffer layer. During the spin coating process, add the antisolvent CB dropwise. After coating, anneal at 120 °C for 30 min to obtain the perovskite light-absorbing layer. Step 16: Take 1.00 g of chitosan, add 100 mL of ultrapure water to fully swell, add 1.2 mL of glacial acetic acid to obtain a transparent viscous solution; slowly add 20 mL of 1.8 mol / L potassium iodide solution, slowly add 1.2 mol / L iodine solution, stir at 25~100℃ for 1 h; slowly pour the reaction mixture into anhydrous ethanol, stir for 1 h to allow the product to precipitate completely, filter out the product, wash and dry to obtain chitosan-polyiodine supramolecular compound; take 0.5 mg of chitosan-polyiodine supramolecular compound and dissolve it in 1 mL of isopropanol to obtain the desired chitosan-polyiodine supramolecular solution; spin-coat it onto the surface of the perovskite light-absorbing layer at 3000 rpm for 30 s, anneal at 100℃ for 5 min to obtain the chitosan-polyiodine supramolecular barrier layer; Step 17: Add 30 μL of PC with a concentration of 20 mg / mL 61 BM's CB solution was dropped onto a chitosan-polyiodine supramolecular barrier layer and spin-coated at 2000 rpm for 30 s. Then, 70 μL of a 0.5 mg / mL BCP IPA solution was dropped onto a PC. 61 On the BM layer, spin coating is performed at 5000 rpm for 30 seconds to obtain the electron transport layer (ETL layer). Step 18: Deposit an Au electrode with a thickness of 60 nm on the surface of the electron transport layer.
9. The method for preparing a perovskite solar cell with a barrier layer as described in claim 7, characterized in that, The steps include the following: Step 21: The substrate of the 2.5*2.5cm indium tin oxide (ITO) transparent conductive electrode is ultrasonically cleaned with deionized water, isopropanol and acetone in sequence for 15 minutes each, then dried with nitrogen and UV treated for 30 minutes. Step 22: Dissolve 9g of nickel(II) nitrate hexahydrate in 120mL of water and stir at room temperature to obtain a clear green solution. Then add 1M sodium hydroxide solution until the pH value is 10. After stirring for 10 minutes, centrifuge to collect the green precipitate. Wash it three times with deionized water and ethanol respectively. Dry the green powder at 80℃ for 12h and then calcine it at 275℃ for 2h to obtain a dark gray powder. Take 200mg of this powder and 30mg of NiI2 powder and dissolve them together in 10mL of DMF to obtain a 3mg / mL NiOx-NiI2 solution. Step 23: Dissolve 200 mg of nickel nitrate in 10 mL of ethanol to obtain a nickel nitrate solution of 20 mg / mL. Filter the solution through a PVDF filter. Spin-coat 1 mL of the 20 mg / mL nickel nitrate solution onto the cleaned ITO layer. Then anneal at 250 °C for 60 min to obtain the hole transport layer (HTL layer). Step 24: Take 1 mL of the prepared NiOx-PbI2 solution and drop it onto the surface of the hole transport layer. Spin coat it at 5000 rpm for 30 s, then anneal it at 100 °C for 10 min to obtain the NiOx-PbI2 buffer layer. Step 25: Dissolve 599 mg of PbI2, 172 mg of MAI, 39 mg of PbCl2 and 46.4 mg of FAI in a mixed solution of 300 μL of DMSO and 700 μL of GBL, and stir at 53 °C for 12 h to obtain a perovskite precursor solution; add 50 μL of the perovskite precursor solution dropwise onto the buffer layer, spin coat at 1500 rpm for 20 s, and then spin coat at 3500 rpm for 40 s; in the last 15 seconds of spin coating, rapidly drop 900 μL of toluene into the film, and finally anneal at 100 °C for 6 minutes to obtain a perovskite light-absorbing layer; Step 26: Take 1.00 g of chitosan, add 100 mL of ultrapure water to fully swell, add 1.2 mL of glacial acetic acid to obtain a transparent viscous solution; slowly add 20 mL of 1.8 mol / L potassium iodide solution, slowly add 1.2 mol / L iodine solution, stir at 25~100℃ for 1 h; slowly pour the reaction mixture into anhydrous ethanol, stir for 1 h to allow the product to precipitate completely, filter out the product, wash and dry to obtain chitosan-polyiodine supramolecular compound; take 0.5 mg of chitosan-polyiodine supramolecular compound and dissolve it in 1 mL of isopropanol to obtain the desired chitosan-polyiodine supramolecular solution; spin-coat it onto the surface of the perovskite light-absorbing layer at 3000 rpm for 30 s, anneal at 100℃ for 5 min to obtain the chitosan-polyiodine supramolecular barrier layer; Step 27: Add 30 μL of PC with a concentration of 20 mg / mL 61 BM's CB solution was dropped onto a chitosan-polyiodine supramolecular barrier layer and spin-coated at 2000 rpm for 30 s. Then, 70 μL of a 0.5 mg / mL BCP IPA solution was dropped onto a PC. 61 On the BM layer, spin coating is performed at 5000 rpm for 30 seconds to obtain the electron transport layer (ETL layer). Step 28: Deposit an Au electrode with a thickness of 60 nm on the surface of the electron transport layer.
10. The method for fabricating a perovskite solar cell with a barrier layer as described in claim 7, characterized in that, The steps include the following: Step 31: The substrate of the 2.5*2.5cm indium tin oxide (ITO) transparent conductive electrode is ultrasonically cleaned with deionized water, isopropanol and acetone in sequence for 15 minutes each, then dried with nitrogen and UV treated for 30 minutes. Step 32: Dissolve 9g of nickel(II) nitrate hexahydrate in 120mL of water and stir at room temperature to obtain a clear green solution. Then add 1M sodium hydroxide solution until the pH value is 10. After stirring for 10 minutes, centrifuge to collect the green precipitate. Wash it three times with deionized water and ethanol respectively. Dry the green powder at 80℃ for 12h and then calcine it at 275℃ for 2h to obtain a dark gray powder. Take 200mg of this powder and 30mg of NiI2 powder and dissolve them together in 10mL of DMF to obtain a 3mg / mL NiOx-NiI2 solution. Step 33: Dissolve 200 mg of nickel nitrate in 10 mL of ethanol to obtain a nickel nitrate solution of 20 mg / mL. Filter the solution through a PVDF filter. Take 1 mL of the 20 mg / mL nickel nitrate solution and spin-coat it onto the cleaned ITO layer. Then anneal at 250 °C for 60 min to obtain the hole transport layer (HTL layer). Step 34: Take 1 mL of the prepared NiOx-PbI2 solution and drop it onto the surface of the hole transport layer. Spin coat it at 5000 rpm for 30 s, then anneal it at 100 °C for 10 min to obtain the NiOx-PbI2 buffer layer. Step 35: Spin-coat a DMF solution of PbI2 onto the surface of the NiOx-NiI2 buffer layer, anneal at 90°C for 30 min, then vapor-deposit CsI on it with a thickness of 400 nm, and anneal at 200°C for 5 min to obtain an inorganic CsPbI3 perovskite light-absorbing layer. Step 36: Take 1.00 g of chitosan, add 100 mL of ultrapure water to fully swell, add 1.2 mL of glacial acetic acid to obtain a transparent viscous solution; slowly add 20 mL of 1.8 mol / L potassium iodide solution, slowly add 1.2 mol / L iodine solution, stir at 25~100℃ for 1 h; slowly pour the reaction mixture into anhydrous ethanol, stir for 1 h to allow the product to precipitate completely, filter out the product, wash and dry to obtain chitosan-polyiodine supramolecular compound; take 0.5 mg of chitosan-polyiodine supramolecular compound and dissolve it in 1 mL of isopropanol to obtain the desired chitosan-polyiodine supramolecular solution; spin-coat it onto the surface of the perovskite light-absorbing layer at 3000 rpm for 30 s, anneal at 100℃ for 5 min to obtain the chitosan-polyiodine supramolecular barrier layer; Step 37: Add 30 μL of PC with a concentration of 20 mg / mL. 61 BM's CB solution was dropped onto a chitosan-polyiodine supramolecular barrier layer and spin-coated at 2000 rpm for 30 s. Then, 70 μL of a 0.5 mg / mL BCP IPA solution was dropped onto a PC. 61 On the BM layer, spin coating is performed at 5000 rpm for 30 seconds to obtain the electron transport layer (ETL layer). Step 38: Deposit an Au electrode with a thickness of 60 nm on the surface of the electron transport layer.